Extractive pax and socio-environmental conflict in Colombia - De Los Ríos, Sebastián (2016)
The government of Colombia and the Revolutionary Armed Forces of Colombia (FARC) have signed agreements heralding an era of “peace” for the country. While the end of the confrontation brings many opportunities, it also poses numerous challenges. This article argues that the most significant of these challenges is the potential for the conflict to merely transform into a socio-environmental conflict. Indeed, the mere signing of the peace agreements does not constitute a guarantee to prevent the escalation of conflict in some regions. To prevent this, the dynamics of dialogue and consensus evidenced in the negotiations that took place in Havana must be replicated at a local level in the territories that once were dominated by the FARC. Improved security conditions deriving from the ceasefire have shown propitious for the development of extractive activities in territories previously ridden by armed conflict. But while the dynamism of the mining and energy sector provides significant opportunity for economic development, it has coincided with the intensification of socio-environmental conflict in several regions of the country. If the government does not address these rising conflicts between multi-nationals and local populations, what is now fertile ground for peacebuilding could prove to be the beginning of a new form of long-lasting violent conflict.